A Web-Based Control And Monitoring System - Firjani, Ahmad Abdusalam (2002)
The Internet has become the latest medium for communication through the advanced features available on the internet such as file transfer, transaction application, advertising and much more. Recent years have been people use it also for remote control and monitoring devices. With advances in the Internet technologies, a lot of electronic goods such as laser printers, fax machines, computers, VCRs, TV, security monitors and other home appliances will be connected by a global network called the Embedded Internet. These systems can be built with improved diagnostic features and flexibility in terms of configuration parameters. Efficient methods of monitoring/configuring such systems are the subject of current research and development. Remote monitoring and configuration of such systems is of great interest and importance A web-based device monitoring and control system has been developed. This project is an integration of three systems, i.e. computer-based control system, Small web server and Internet . This integration is achieved by the use of the small web server and a designed web page using HTML, SiteObject, java script and java applet. The developed system when connected to the network via another network or internet allows users to remotely control and monitoring home appliances. The device can be controlled via serial port of the small server and can be controlled through the designed web page. A server program was installed in the web server to instruct the small web server to perform a particular function.